A multi-cohort study of ApoE ɛ4 and Amyloid-β effects on the hippocampus in Alzheimer’s Disease - Khan, Wasim; Banaschewski, Tobias; Flor, Herta; Rietschel, Marcella (Journal of Alzheimer's disease, 2017)
The apolipoprotein E (APOE) gene has been consistently shown to modulate the risk of Alzheimer’s disease (AD). Here, using an AD and normal aging dataset primarily consisting of three AD multi-center studies (n = 1,781), we compared the effect of AP
Gesehen am 18.04.2018